First Year Science in a Commuter University: Where to Intervene - Grayson, J. Paul (Canadian Journal of Higher Education, 1994)
A study of first year science students in a large Canadian commuter university shows that integration/involvement variables are important in explaining a number of desired outcomes. Most evident is the fact that students who were satisfied with the quality of instruction, and students who felt that topics covered in classes were important to future career success, were more likely than others to score high on a number of desired outcomes. By way of comparison, variables falling in the social integration/involvement category, by and large, were not important in explaining desired outcomes. For example, in contrast to previous findings on factors affecting student development, the number of out- of-class contacts with faculty had no impact on any of the outcomes under consideration Overall, the findings, and possible avenues of improvement that they suggest, reflect the fact that in a large commuter university classroom contact represents the main link between the institution and the individual. As a result, it is likely that improvements in curriculum and teaching would have large payoffs for both students and the institution. The university under study is a commuter university in a large city with large first year science classes. Where similar conditions can be found in other Canadian universities, it is likely that various outcomes can be explained by reference to similar factors. By extension, it is equally probable that changes likely to enhance outcomes would also lead to improvements elsewhere.